1986
DOI: 10.1099/00221287-132-5-1319
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen and Trehalose Accumulation during Colony Development in Streptomyces antibioticus

Abstract: ~ ~~ ~Streptomyces antibioticus accumulated glycogen and trehalose in a characteristic way during growth on solid medium. Glycogen storage in the substrate mycelium took place during development of the aerial mycelium. The concentration of nitrogen source in the culture medium influenced the time at which accumulation started as well as the maximum levels of polysaccharide stored. Degradation of these glycogen reserves was observed near the beginning of sporulation. The onset of sporogenesis was always accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…On the other hand, Glc-1P is the initial metabolite of routes allowing sugar/NDP-sugar interconversion, synthesis of oligoand polysaccharide structural components, or production of reserve glucans (glycogen) (12,32). A critical point determining metabolic fates for Glc-1P/Glc-6P within a cell is the presence or absence of UDP-sugar PPase, an enzyme that so far has been found in plants and protozoa (15,16,22,26,28,29,41).…”
Section: Figmentioning
confidence: 99%
“…On the other hand, Glc-1P is the initial metabolite of routes allowing sugar/NDP-sugar interconversion, synthesis of oligoand polysaccharide structural components, or production of reserve glucans (glycogen) (12,32). A critical point determining metabolic fates for Glc-1P/Glc-6P within a cell is the presence or absence of UDP-sugar PPase, an enzyme that so far has been found in plants and protozoa (15,16,22,26,28,29,41).…”
Section: Figmentioning
confidence: 99%
“…DISCUSSION Trehalose is present in large quantities in S. griseus and is most abundant in spores in which it may enhance spore resistance (1,4,(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…Nongerminating spores of Streptomyces viridochromogenes, Streptomyces antibioticus, and Micromonospora echinospora and nongrowing spherical cells of Arthrobacter crystalopoietes and Nocardia coralina also maintained large amounts of trehalose and active trehalase. These trehalose reserves were depleted during spore germination or outgrowth of spherical Arthrobacter and Nocardia cells into rods.Large amounts of the disaccharide trehalose are present in the dormant spores or cysts of a variety of organisms including actinomycetes, fungi, nematodes, and brine shrimp (1,3,5,6,18). Trehalose is degraded very slowly by these organisms during periods of dormancy but is rapidly metabolized following the onset of vegetative growth (2,11,20,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The content of trehalose in aerial spores was higher than in the submerged spores. It has been reported that trehalose is the major carbohydrate in Streptomyces spores (Ensign, 1978;Brana et al, 1986), and also that the resistance of actinomycete spores to heat and desiccation is linked closely to their content of trehalose (Kendrick & Ensign, 1983;Dworkin, 1985;McBride & Ensign, 1987a, b).…”
Section: Discussionmentioning
confidence: 99%